Intravascular Papillary Endothelial Hyperplasia of the Orbit: A Case of Masson’s Tumor - Dryden, Stephen C (Cureus, 2019)
Herein, we present a case of a 64-year-old male presenting with diplopia that was found to have a left orbital Masson’s tumor. It is necessary to differentiate it from malignant angiosarcoma as complete excision is often curative. The following case emphasizes the modalities that can be used for diagnosis as well as the appropriate treatments.